Ecological Impact on the Prevalence of Giant Scale Insect (Homoptera : Monophlebidae) in Jahangirnagar University Campus, Bangladesh: Ecological Impact on the Prevalence of Giant Scale Insect (Homoptera : Monophlebidae) - Chowdhury, Ibna Zayed; Rahman, G M Saifur (Journal of the Asiatic Society of Bangladesh, Science, 2025)
Most monophlebid insects are highly polyphagous, dimorphic, and well-known sap-sucking plant pests throughout the world. To determine their abundances, distribution, incidences, seasonal dynamics, feeding nature and the effects of ecological changes on their populations, an initial study (September 2004–August 2005) and a review study (March 2023–February 2024) were carried out in Jahangirnagar University Campus (JUC), Savar, Dhaka, Bangladesh. The host plants (trees and shrubs) were examined through biweekly visual counts. In the initial investigation, 14,802 monophlebid insects from three species (Biodiversity Index or BI = 0.002, H = 1, D = 0.387, 1-D = 0.613, 1/D = 2.58, and EH = 0.91) were documented from 10 plant species. In the review study, a total of 423 insects under five species (two previously identified and three new) (BI = 0.141, H = 0.22, D = 0.917, 1-D = 0.083, 1/D = 1.1, and EH = 0.14) detected from five plant species, including one new species. Within around 20 years from the first study, the percentage of total plants and infested plants decreased significantly by 47.14% and 92.96%, respectively. The amount of insects decreased by 2.86%, while 87.67% of shrubs decreased (F = 5.8, df = 1, P = 0.07). The pest insects from trees and shrubs reduced by 3.67% and 0.45%, respectively. The identified most suitable host plant was Ficus benghalensis for sheltering maximum scale insect in both studies. The only insect pest, Icerya aegyptiaca was consistently abundant throughout the period in both studies. The insect, I. aegyptiaca was found available on every part of the plant, though the majority of them survived on leaves. The present findings might contribute understanding ecological imbalances and helpful for developing effective management strategies against these insect pests. J. Asiat. Soc. Bangladesh, Sci. 50(1-2): 51-67, June-December 2024